Defining estuarine squeeze: The loss of upper estuarine transitional zones against in-channel barriers through saline intrusion. (5th November 2022) - Little, Sally; Lewis, Jonathan P.; Pietkiewicz, Helen
Abstract: Here we define, for the first time, the concept of estuarine squeeze and lay out recommendations for the consistent use of terminology for this new but critical research area. Climate and catchment-driven reductions in river flow together with rising sea levels are increasing estuarine salinities and driving saltwater into upper estuarine zones. This saline intrusion is exacerbated in regions where land level is falling (i.e. relative sea level rise) and in catchments subject to high freshwater demand and water regulation, which reduces river flow. In unmodified systems, many estuaries would naturally migrate inland in response to sea level rise. However, estuaries are some of the most anthropogenically impacted ecosystems in the world, being settlement and development hubs due to the ecosystem services they provide. To protect these assets, many estuaries have man-made in-channel barriers (such as dams, weirs and sluices) at their inland tidal limits, a trend that is likely to continue in the future to protect against the impacts of climate change. As sea levels rise and river flows reduce, saltwater will move further inland. This increasing saline intrusion will be most detrimental for upper estuarine, low salinity (oligohaline) and tidal freshwater zones, which will progressively become 'squeezed out' against these barriers. We have termed this concept 'estuarine squeeze' and define this as 'the progressive loss of extent of upper estuarine tidal freshwater and oligohaline zones against in-channel man-made barriers through saline intrusion and increasing salinities driven by relative sea level rise and/or reductions in river flow'. A lack of research into the structure and functioning of tidal freshwater zones in particular means that the impact of their reduction and/or loss on the wider estuary is unknown. However, there are indications that these zones may play a key role in estuarine biogeochemical cycling, habitat provision, primary and secondary production, food-web functioning, and the provision of trophic subsidies to the brackish estuary and coastal zone. Loss and/or reduction of these zones through estuarine squeeze may therefore result in a net loss of function, with critical implications for the ability of estuaries to continue to provide key ecosystem services into the future. Highlights: We introduce and define the new concept of estuarine squeeze. Estuarine squeeze is caused by climate change, sea level and man-made barriers. Oligohaline and tidal freshwater zones are most at risk from estuarine squeeze. These zones may play a key role in estuarine connectivity and functioning. Estuarine squeeze may reduce the ability of estuaries to provide key services.